CONFORTO TÉRMICO DE EDIFÍCIO ESCOLAR PADRÃO PROINFÂNCIA TIPO B EM TRÊS REGIÕES BIOCLIMÁTICAS BRASILEIRAS DISTINTAS - Spagnuolo, Augusto Yuji Nojima; Silveira, Guilherme Willian Petrini da; Serrano, Alessandra da Costa; Faria, Obede Borges; Magagnin, Renata Cardoso (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Environmental comfort is an important feature for public buildings, especially those built in series by governmental programs. Between 2007 and 2017 the Proinfância program built 3314 kindergartens of the Type B project in 8 Brazilian bioclimatic zones. The objective of this paper is to evaluate if these projects are thermally comfortable in three distinct Bioclimatic Zones (BZ). It was carried out using thermal simulation with the Energyplus software in Canela-RS (BZ- 1), Belém-PA (BZ-8) and Sorocaba-SP (BZ-3) with two different hypothetical orientations and extracted the operating temperatures of a reference room. The values was analyzed in comparison to the Adaptive Comfort Temperature of each locality and the results indicated that, in the average hours of use, 27% are in discomfort mainly for cold in Canela-RS, 43% in discomfort for heat in Belém-PA and 84% are in comfort in Sorocaba-SP. In the comparison of the orientation of buildings, it was observed that there is a variation of results in Belém-PA and a minimum variation in Canela-RS and Sorocaba-SP, related to the direct insulation of the envelope. The present study demonstrates that the adoption of standard designs, without modifications in implantation and in the envelope is an inadequate strategy to attend thermal comfort.